The Role of CPEC in the Economic Development of Gwadar: A Case Study (Journal of Asian Development Studies, 2025)
Many projects like development of blue deep-sea port, development of economic zones, Eastbay expressway, Pak-China friendship hospital, 300MW Coal-Fired Power Project, 5MGD Water Desalination Plant and new Gwadar international airport works have been started in Gwadar. These projects are being constructed for the development of Gwadar under the China-Pakistan Economic Corridor. The China Pakistan Economic Corridor a game changer for economic growth. This paper finds out whether these mega projects really a fate changer for the locals of Gwadar or not. Therefore, this research article aimed at exploring the central role of CPEC in economic development of the port city. This conducted research study is a mixed type of research, containing both qualitative and quantitative methods to make the research article more reliable. This research is based on both primary and secondary sources. The secondary data was collected through books, scholarly articles, websites, and the primary data was collected through questionnaires from the natives of Gwadar. District Gwadar was selected as the sample size of the research study 120 participants participated in the study survey. Seven questions were distributed to 120 respondents of the locals of Gwadar in order to know their opinions about the importance of CPEC development for the indigenous of Gwadar.